Synthesis of new polyhedral oligomeric silsesquioxane derivatives as some possible antimicrobial agents - Ersoy, Elif Basak; Gunkara, Omer Tahir; Ocal, Nuket (TAYLOR & FRANCIS LTD, 2019)
1,3-Dipolar cycloaddition reactions were studied to synthesize Polyhedral oligomeric silsesquioxane (POSS)-based norbornyl imide derivatives containing izoxazoline groups in good yields. And also 1,3-dipolar cycloaddition reactions of azomethine ylides with POSS-based norbornene dipolarophiles for a synthesis of the novel POSS-based norbornane-fused spiro-1,3-indandionolylpyrrolidines are reported. All newly synthesized POSS compounds were structurally characterized by FTIR, H-1, C-13 NMR, HRMS and GC/MS analyses.
Keywords: 1,3-Dipolar cycloaddition; azomethine ylide; coating material; polysiloxanes; polyhedral oligomeric silsesquioxane (POSS); 1,3-DIPOLAR CYCLOADDITION REACTIONS; NITRILE OXIDES; HYBRID NANOCOMPOSITES; THERMAL-PROPERTIES; POLYMERS; REGIOSELECTIVITY; HETEROCYCLES; Chemistry